Investigation of the electrochromic properties of Ni(OH)2 films on glass with ITONi bilayer coating - Kotok, Valerii; Kovalenko, Vadym (Eastern-European Journal of Enterprise Technologies, 2018)
Electrochromic films have been deposited onto glass coated with indium-tin oxide (ITO) and glass with ITO and a thin layer of metallic nickel deposited onto it. Nickel was deposited onto the surface of the ITO coating from nickel electroplating solution. The metallic nickel was deposited onto the surface of ITO at the following parameters – cathodic current density 0.5 A/dn2, deposition time 3 s. Such deposition parameters were chosen, because at longer deposition time and (or) higher current density, the deposited layer of metallic nickel became opaque. The two substrates were then used in the deposition of Ni(OH)2 electrochromic films using the cathodic template synthesis method. As a result, it was revealed that the electrochromic film deposited onto glass with ITO-Ni coating possesses higher specific characteristics than that deposited on bare ITO-coated glass: higher coloration degree and higher oxidation-reduction currents on the cyclic voltamperogram. However, it was also revealed that the film possessing better characteristics, on the contrary, has lower reversibility of the coloration-bleaching process. Based on the obtained data, the mechanism that explains the role of the intermediate metal layer was proposed. The mechanism is that the deposited layer of metallic nickel forms additional contacts between the substrate surface and the electrochromic film. The nickel layer can also assist in securing the electrochromic film, and during film deposition has a positive effect on current distribution. On the other hand, the lower reversibility of the coloration-bleaching process of the film on ITO-Ni coating can be explained by gradual oxidation of metallic nickel in the basic medium. At the same time, it was revealed that deposition of metallic nickel leads to some decrease of the substrate transparency.